Impact of production linkages on industrial upgrading in ASEAN, the People's Republic of China, and India: Organizational evidence of a global supply chain - Tomohiro Machikita; Yasushi Ueki (Asian Development Bank Institute (ADBI), 2012)
This paper presents a simple model of industrial upgrading as a result of backward and forward information linkages between upstream and downstream relations. It also serves as an empirical investigation of the impact of mutual knowledge exchange on the knowledge production function using data on firms' self-reported customers and suppliers. Evidence from interconnected firms in Indonesia, Thailand, Philippines, and Viet Nam suggests that there are strong spillover effects between downstream and upstream firms in terms of international standard certification. The degree of product and process innovation is quite diverse across manufacturing firms within a local supply chain and within a global supply chain. Firms are likely to achieve product innovation if they have customers in foreign countries. Customers in Japan and the People's Republic of China play an important product innovation role for firms in Association of Southeast Asian Nations (ASEAN) economies, and customers in the United States or Europe play an important industrial upgrading role in connecting ASEAN firms with the global market.
Keywords: O31; O32; R12; 330; innovation; international production organization; backward forward linkages; Regionale Wirtschaftsintegration; Internationale Arbeitsteilung; Industrieproduktion; Industrieproduktion; ASEAN-Staaten; China; Indien